Numerical simulation and analysis on the mechanical responses of the urban existing subway tunnel during the rising groundwater. (April 2020) - Lu, Dechun; Li, Xiaoqiang; Du, Xiuli; Lin, Qingtao; Gong, Qiuming
Abstract: In this paper, a numerical method of the rising groundwater level is presented through an elastoplastic constitutive model for the unsaturated soil and a numerical realization method for the rising groundwater level. A model test of the rising groundwater level is conducted to validate the rationality of the presented numerical method. Taking an interval subway tunnel in Beijing as the background, a numerical simulation with a homogeneous soil layer, which contians the existing tunnel, is conducted according to the presented numerical method of the rising groundwater level. Based on the numerical simulation results, the variations of the ground saturation, the ground stress state, and the ground vertical deformation under the condition of the rising groundwater level are studied through a homogeneous soil layer, and the normal contact pressure on the outer surface of the lining, the radial deformation, the bending moment, the hoop thrust, and the shear force of the lining under the condition of the rising groundwater level are analyzed through a homogeneous soil layer with the existing tunnel.